Sensitivity and improvement of in vitro methods to assess the effects of Saccharomyces cerevisiae on rumen fibre degradation - Russouw, Aimee (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.